PERLINDUNGAN HUKUM INTERNET SERVICE PROVIDER TERHADAP PENYALAHGUNAAN BANDWIDTH PADA PRODUK HOME IDPLAY - Retno Apriyani Tijas; Arikha Saputra (Legal Standing : Jurnal Ilmu Hukum, 2023)
Many Indonesian people use internet services, one of which is by registering for installation at home from the company PT. Trans Indonesia Supercorridor, this company is a solution to access broadband internet connection. One of the products from PT. Trans Indonesia Supercorridor is a product of Idplay. Some consumers intentionally default on PT. Trans Indonesia Supercorridor by reason of wanting to seek more profit with not much capital, such as reselling the internet it uses to other people, where in the agreement consumers are prohibited from reselling it to other people. The research method used is normative legal research. Based on the specifications of this paper which uses an in concerto research method, the data analysis used is a qualitative approach to secondary data, which means that it includes the content and structure of positive law. Protection carried out by PT. Trans Indonesia Supercorridor (TIS). namely preventive protection such as by reprimanding Mr. X, then PT.TIS also performs repressive protection, namely by terminating Mr. X's internet cable network. The form of sanctions given by PT.TIS to consumers is to ask for compensation by make payments due to bandwidth abuse, but if consumers cannot make compensation in the form of payments according to the amount of losses suffered by PT. TIS then the action taken by PT.TIS is to withdraw the device (ONU) to the consumer.